Reformasi Birokrasi dan Pemenuhan Hak Warga dalam Mengakses Pelayanan Publik melalui Mal Pelayanan Publik - Ade Harsa Suryanegara (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
Various services are organized to meet the needs and provide convenience for the community. In the reform era, through the ministry of Administrative Reform and Bureaucratic Reform, one of the efforts to improve the quality of public services is to formulate policies in the form of Public Service Mall. This paper discusses the government's efforts to improve bureaucratic reform through the implementation of Public Service Malls. The issue of licensing is a complicated process that makes it difficult for the public to access public services. Hence, people are reluctant to deal with administrative issues. With an integrated Public Service Mall one door to serve a variety of administrative services, licensing services can be provided in a prime, effective and efficient manner.